The effect of guide vane type on performance of multistage energy recovery hydraulic turbine (MERHT) - Tian Yabin; Hu Anjie; Zheng Qi (Open Physics, 2020)
In this work, we theoretically analyzed the main factors affecting performance of multistage energy recovery hydraulic turbine (MERHT), and found that the arc radius (r) of the edge at the outlet section of the runner guide vane is the determining factor of the hydraulic efficiency of hydraulic turbines. To further improve the performance of the MERHT, a numerical model is then proposed to optimize the arc radius. The MERHT-type DCSGT250-175 × 9 was taken in the simulation. The hydraulic efficiency η h and the corresponding distributions of pressure and velocity were numerically studied with four different values of r ranging from 133.5 to 138 mm. It is found that the flow state and the flow field distribution were the best when r equals to 134 mm. With the optimum r, the external diameter of the runner guide vane (D) was further adjusted, which can lead to 3.9% increase of average efficiency according to the simulation results.